Food systems governance e-course – SHiFT work package 5 evaluation report - Groote, Bram de; Olaerts, Astrid; Herens, Marion C.; Dengerink, Just; Namugumya Shenute, Brenda; ten Hove, Hermine (International Food Policy Research Institute, 2023)
The food systems approach is increasingly being used to understand the dynamics of how food is produced and consumed, with an optimal outcome for human health, social justice, economic endeavors, and the preservation of planetary resources. Since the United Nations Food Systems Summit (UNFSS) in September 2021, the food systems approach has become central to policy and practice of many international development and research organizations, multilateral organizations, and in (national) programs and policies aiming at improving food and nutrition security.